52 km-Long Transmission Link Using a 50 Gb/s O-Band Silicon Microring Modulator Co-Packaged With a 1V-CMOS Driver - Miltiadis Moralis-Pegios; Stelios Pitris; Theoni Alexoudi; Hannes Ramon; Xin Yin; Johan Bauwelinck; Yoojin Ban; Peter De Heyn; Joris Van Campenhout; Nikos Pleros (IEEE Photonics Journal, 2019)
We present an O-band silicon microring modulator with up to 50 Gb/s modulation rates, co-packaged with a 1V-CMOS driver in a dispersion un-compensated, transmission experiment through 52 km of standard single-mode fiber. The experimental results show 10−9 error-rate operation with a negligible power penalty of 0.2 dB for 40 Gb/s and wide-open eye diagrams for 50 Gb/s data, corresponding to a record high bandwidth-distance product of 2600 Gb·km/s. A comparative analysis between the proposed transmitter assembly and a commercial LiNbO3 modulator revealed a moderate increase of 3.8 dB in power penalty, requiring only 20% of the driving voltage level used by the commercial modulator.